Interaction of magnesium with potassium in sugarcane - Garcia, Ariani [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The aim of this study was to evaluate the effect of Mg2+ and K+ concentrations, and Mg2+ foliar application on the root and shoot growth, as well as to check the alterations on the nutritional status and carbohydrates partitioning in sugarcane plants. For this purpose, three studies were conducted: i) evaluation of the effect of Mg2+ concentrations (adequate and deficient) on the sugarcane plants development; ii) metabolic and nutritional alterations in sugarcane due to Mg2+ imbalance caused by K+ high level; iii) efficiency of the Mg2+ foliar application in sugarcane plants grown under varied levels of K+ and Mg2+. The experiments were estabilished in greenhouse and the plants grown in nutrition solution. The evalutions were: leaf chlorophyll content, root morphological parameters (length and root diameter), dry matter production of plant parts, nutritional composition and starch, sucrose and reducing sugars partitioning in the different plant parts. In general, the adequate supply of Mg2+ resulted in higher dry matter production, sucrose concentration in the stalks and root/shoot ratio. Chlorophyll a, b and carotenoids were lower in Mg2+ deficient plants. Moreover, higher concentration of starch and soluble sugars were observed in the leaves and lower starch concentration in the stalks of these plants. Besides, Mg-deficient plants had shorter root length and larger diameter, which presented higher K+ concentrations in the root and higher translocation of this cation to the shoot. Increase in K+ concentration in the nutrition solution reduced Mg2+ concentration in the roots, young leaves, old leaves and stalks of sugarcane, even in Mg2+ control plants. Regardless Mg2+ nutrition, at the highest level of K+, all the plant growth parameters evaluated in this study were reduced. Plants grown under Mg2+ deficiency obtained higher starch concentration in the stalks at higher K+ level. Magnesium foliar application raised the sucrose concentration in the stalks and reduced the starch, regardless the K+ level evaluated. In addition, bigger plants were observed with foliar application and high K+ level, at both Mg2+ levels. For the plant growth parameters, with or without foliar application, Mg2+ deficiency seemed to greater affect the sugarcane plants than the high levels of K+.

Objetivou-se avaliar o efeito do fornecimento de concentrações de Mg2+e K+ , e da aplicação foliar de Mg2+ no desenvolvimento da raiz e parte aérea, bem como possíveis alterações no estado nutricional e na partição de carboidratos em plantas de cana-de-açúcar. Para tanto, três estudos foram conduzidos: i) avaliação do efeito de concentrações de Mg2+ (controle e deficiente) no desenvolvimento de plantas de cana-de-açúcar; ii) alterações metabólicas e nutricionais na cana-de-açúcar decorrentes do desequilíbrio de Mg2+ causado pelo alto nível de K+ ; iii) eficiência da aplicação foliar de Mg2+ em plantas de cana-de-açúcar cultivadas em nutrição variada de K+ e Mg2+. Os experimentos foram conduzidos em casa de vegetação e as plantas cultivadas em solução nutritiva. Foram avaliados: o teor de clorofila nas folhas, parâmetros morfológicos das raízes (comprimento e diâmetro radicular), produção de matéria seca das partes da planta, composição nutricional e partição de amido, sacarose e açúcares redutores nas diferentes partes da planta. No geral, o adequado fornecimento de Mg2+ levou a maior produção de matéria seca, concentração de sacarose nos colmos e relação raiz/parte aérea. Clorofila a, b e carotenoides foram menores em plantas deficientes em Mg2+. Ademais, foi observado maior concentração de amido e açúcares solúveis nas folhas e menor concentração de sacarose nos colmos destas plantas. Além disso, plantas deficientes em Mg2+ tiveram menor comprimento radicular e maior diâmetro, do que as quais apresentaram maior concentração de K+ na raiz e maior translocação deste cátion para a parte aérea. O aumento da concentração de K+ na solução nutritiva reduziu a concentração de Mg2+ nas raízes, folhas novas, folhas velhas e colmos da cana-de-açúcar, mesmo nas plantas controle de Mg2+. Independente da nutrição com Mg2+, no maior nível de K+ , todos os parâmetros biométricos avaliados neste estudo foram reduzidos. Plantas cultivadas sob deficiência de Mg2+ obtiveram maior concentração de amido nos colmos em altas concentrações de K+ . A aplicação foliar de Mg2+ aumentou o conteúdo de sacarose nos colmos e reduziu o de amido, independentemente do nível de K+ avaliado. Além disso, foi observado plantas maiores com a aplicação foliar e alto nível de K, em ambos níveis de Mg2+ avaliados. Para os parâmetros biométricos, com ou sem aplicação foliar, a deficiência de Mg2+ pareceu afetar mais as plantas de canade-açúcar do que os altos níveis de K+ .
Interação do magnésio com o potássio na cana-de-açúcar
Keywords: Saccharum spp.; Carbohydrate partitioning; Chlorophyll production; Nutritional status; Potassium; Partição de carboidratos; Produção de clorofila; Estado nutricional; Nutrição de plantas; Potássio